Coriolis effect on thermal convection in a rotating bidispersive porous layer. (25th March 2020) - Capone, F.; De Luca, R.; Gentile, M.
Abstract : We obtain the linear instability and nonlinear stability thresholds for a problem of thermal convection in a rotating bidispersive porous medium with a single temperature. We show that the linear instability threshold is the same as the nonlinear stability one. This means that the linear theory is capturing completely the physics of the onset of thermal convection.